2019
DOI: 10.33545/surgery.2019.v3.i3a.147
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of incidence, etiology and risk factors associated in acute burns injury in adults

Abstract: Introduction: Burn injuries have major health problem because of its high, morbidity, disability and mortality in young and middle-age people. Burn injuries also have social problems associated with it. It may be associated with accidental, suicidal or homicidal causes. Despite of such importance of burn injuries from clinical and social point of view, there is scarcity of research on burn injuries in India. Thus we tried to highlight our observations in this study which had been undertaken to find out the cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…In our study, it shows similarity with the literature by drawing a more intense profile in men. Considering the age distribution in these studies, it was seen that the most affected group was in the 20-50 age range (8)(9)(10)(11). In our study, we found the mean age to be 35±18 years and it was similar to the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, it shows similarity with the literature by drawing a more intense profile in men. Considering the age distribution in these studies, it was seen that the most affected group was in the 20-50 age range (8)(9)(10)(11). In our study, we found the mean age to be 35±18 years and it was similar to the literature.…”
Section: Discussionsupporting
confidence: 88%
“…With the developing treatment methods and the establishment of burn centers, the mortality rate in burns is also decreasing. In the study conducted by (9)(10)(11). It is seen that burns are more common in men than women, but the rates vary according to regions and countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the hypodermis layer, the thickness is less than 1 mm and decreased with age [6,10,11]. In skin, burn injuries are primarily caused by open flame cooking, stoves, accidents, and cylinder explosions [10,12]. Burns that are severe, need a skin graft during the healing process, which is produced by surgically removing a small section of healthy donor skin and expanding it mechanically to cover the larger affected area [13].…”
Section: Introductionmentioning
confidence: 99%